The Role Of Point-Of-Care Testing In The Rapid Diagnosis Of Catastropic Disease Emergencies - Hutomo, Yugi Tri (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Catastrophic diseases, such as heart attack, stroke, or septic shock, are emergency conditions that require prompt diagnosis and proper treatment. One promising approach to speed up diagnosis is the use of Point-of-Care Testing (POCT), which allows diagnostic test results to be obtained directly at the point of care. The purpose of this study is to evaluate the role of POCT in the rapid diagnosis of catastrophic diseases in emergency patients and to determine its impact on the speed of medical decision-making as well as clinical outcomes of patients. This study uses an observational research design with a prospective approach in patients with suspected catastrophic diseases who are treated in the emergency department (ER). Data were collected from patients undergoing POCT in the ER and compared with conventional diagnostic results. Univariate and bivariate analyses were performed to evaluate the relationship between the use of POCT and the time to diagnosis, decision-making, and clinical outcomes of patients. Statistical tests using t-or chi-square tests for comparison between groups with univariate analysis results showed that the use of POCT significantly accelerated the time to diagnosis (p<0.05) compared to conventional diagnostic methods. In addition, the use of POCT results in faster and more precise treatment decisions. In bivariate analysis, there was a significant association between the use of POCT and improved patient clinical outcomes, such as reduced mortality rates and shorter recovery times. Patients who get a quick diagnosis using POCT show faster and better improvement in their condition. In contrast, in patients who do not use POCT, late diagnosis often results in decreased organ function and further complications with POCT conclusions play an important role in the rapid diagnosis of catastrophic diseases in the ER and can improve the speed of medical decision-making and improve the patient's clinical outcomes.